Implementation of Party-State Social Programme in 1960ies-1980ies: Housing Construction in Ulyanovsk and Dimitrovgrad - R. A. Mukhamedov; N. S. Boyko; M. I. Khisamov (Научный диалог)
The article analyzes the features of the formation and development of the construction industry in the Ulyanovsk region in the 1960-80ies, as well as the state of the material and technical base of construction. The relevance of the study is due to both the historiographical lacuna on this topic and the degree of high social significance of the housing construction sector. A detailed analysis of the housing policy of local authorities in Ulyanovsk and Dimitrovgrad is necessary to recreate the historical reality that has developed in the region during this period. The main difficulties of implementing the programme of mass housing construction are revealed. Archival data from the funds of the State archive of the Ulyanovsk region and the State archive of the modern history of the Ulyanovsk region are introduced into scientific circulation, materials of the periodical press are involved. It is noted that the construction was characterized by construction monotony, questionable architectural value of buildings, allowed irrational layout of housing: small apartments with low ceilings, small kitchens, walk-through rooms. The authors claim that the campaign initiated by the local party bodies in the 1960ies-1980ies to build residential quarters in Ulyanovsk and Dimitrovgrad helped to significantly relieve tensions in the housing sector: the population was provided with comfortable housing, resettlement from communal apartments, barracks, dilapidated housing was carried out.